First be nimble : a story about how to adapt, innovate and perform in a volatile business world - Winter, Graham (John Wiley & Sons, 2012)
The how-to guide to building an adaptive, productive business environment Graham Winter, author of the best-selling Think One Team, brings you First Be Nimble: A Story about How to Adapt, Innovate and Perform in a Volatile Business World. This book addresses the challenge of how to equip businesses to adapt and thrive in an unpredictable and demanding economy. Told in the form of a fable and illustrated with case studies and powerful tools, the book is designed to engage, inspire, and inform readers from all walks of business life. Helping leaders, teams, and whole.